2009
DOI: 10.1097/qad.0b013e3283269dfb
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and metabolic abnormalities in vertically HIV-infected children and youth

Abstract: Objective-To compare the distribution of lipid and glucose abnormalities and altered fat distribution among vertically HIV-infected subjects and controls.Design-Cross-sectional multicenter study in HIV-infected (HIVpos) subjects 7-24 years, stratified by Tanner stage and protease inhibitor (PI) use (PI; N=161 and non-PI; N=79) and seronegative controls (HIVneg; N=146).Methods-Measurements included fasting lipids, glucose, insulin, 2-h oral glucose tolerance test, dual-energy X-ray absorptiometry, anthropometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
113
5
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(130 citation statements)
references
References 62 publications
11
113
5
1
Order By: Relevance
“…These findings are similar to those reported by Werner, Fonseca and Chaves (24) and Aldrovandi et al (25) Altered glucose metabolism, which can be affected by coinfection with the hepatitis C virus, use of protease inhibitors, presence of lipodystrophy, and a family history of diabetes mellitus, among other factors, is more common in adults (26) .…”
Section: Discussionsupporting
confidence: 80%
“…These findings are similar to those reported by Werner, Fonseca and Chaves (24) and Aldrovandi et al (25) Altered glucose metabolism, which can be affected by coinfection with the hepatitis C virus, use of protease inhibitors, presence of lipodystrophy, and a family history of diabetes mellitus, among other factors, is more common in adults (26) .…”
Section: Discussionsupporting
confidence: 80%
“…For example, for a 6-year-old boy with a WAZ score of −0.78 (median at the time of database freeze), the 0.25 difference in z scores at year 5 predicted by adjusted ITT analyses translates to a weight difference of approximately 0.7 kg. Reasons for these findings may include the poor palatability ( particularly with liquid formulations), appetite suppression, and metabolic effects associated with LPV/r and other protease inhibitors [23][24][25]. Interestingly, despite the reputation of liquid LPV/r formulations for challenging administration, the IM-PAACT P1060 trial demonstrated remarkable acceptability and adherence among these young infants, with desirable short-and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia, particularly LDL-C >130 mg/dL, has been associated with an elevated risk of cardiovascular disease. 13 We found low HDL-cholesterol values in 64(46%) cases in our study. 42 out of 93(45%) were in ART group and 22 out of 47(47%) in non-ART group.…”
mentioning
confidence: 59%